Training and standardization of general practitioners in the use of lung ultrasound for the diagnosis of pediatric pneumonia. Issue 11 (20th August 2019) - Pervaiz, Farhan; Hossen, Shakir; Chavez, Miguel A.; Miele, Catherine H.; Moulton, Lawrence H.; McCollum, Eric D.; Roy, Arun D.; Chowdhury, Nabidul H.; Ahmed, Salahuddin; Begum, Nazma; Quaiyum, Abdul; Santosham, Mathuram; et al.
Abstract: Background: Pneumonia is a leading cause of death in children of low‐resource settings. Barriers to care include an early and accurate diagnosis. Lung ultrasound is a novel tool for the identification of pediatric pneumonia; however, there is currently no standardized approach to train in image acquisition and interpretation of findings in epidemiological studies. We developed a training program for physicians with limited ultrasound experience on how to use ultrasound for the diagnosis of pediatric pneumonia and how to standardize image interpretation using a panel of readers. Methods: Twenty‐five physicians participating in the training program conducted lung ultrasounds in all children with suspected pneumonia, aged 3 to 35 months, presenting to three subdistrict hospitals in Sylhet, Bangladesh, between June 2015 and September 2017. Results: A total of 9051 pediatric lung ultrasound assessments were conducted through 27 months of data collection. Study physicians underwent training and all were successfully standardized, achieving 91% agreement and maintained a sensitivity and specificity of 88% and 92%, respectively, when their diagnosis was compared with experts. Overall kappa between two readers was high (0.86, 95% confidence interval [CI], 0.84‐0.87), and remained high when a third expert reader was included (0.80, 95% CI, 0.79‐0.81). Agreement and kappa statistics were similarly high when stratified by age, sex, presence of danger signs, or hypoxemia. Conclusions: Lung ultrasound is a novel tool for the diagnosis of pediatric pneumonia with evidence supporting its validity and feasibility of implementation. Here we introduced a training program that resulted in a high level of inter‐sonographer agreement.